ANALYSIS OF PRODUCT QUALITY AND SERVICE QUALITY FACTORS ON CONSUMER SATISFACTION (A case study at the Kremes Chicken Restaurant in Purwodadi) - Fidyah Yuli Ernawati; Arini Novandalina; Dwi Tsaniyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
In the Era of Globalization which has demanded a change in the old paradigm in all fields, one of which is a change in the modern business world. The increasingly fierce competition requires business people to maximize their performance through product quality and service quality in order to survive in business competition in creating customer satisfaction. For companies, customer satisfaction is one of the most important things in a product or service. The purpose of this study was to determine the effect of product quality and service quality on customer satisfaction at the Ayam Kremes Purwodadi restaurant The population in this study were all consumers of Ayam Kremes Purwodadi restaurant in October as many as 1000 consumers. So that the sample obtained amounted to 70 respondents. The variable in this study is the independent variable (X) consisting of product quality, service quality and the dependent variable (Y) namely consumer satisfaction. Data collection method is done by distributing questionnaires. The method of analysis is the classical assumption test, multiple linear regression test, and hypothesis testing From the research results show that the product quality variable has a significant effect on consumer satisfaction with a significant amount of 0.014 < 0.05. Service quality has a significant effect on customer satisfaction by 0.027